In-situ synchrotron X-ray diffraction during quenching and tempering of SAE 52100 steel. (December 2021) - Foster, D.; Paladugu, M.; Hughes, J.; Kapousidou, M.; Islam, U.; Stark, A.; Schell, N.; Jimenez-Melero, E.
Abstract: The quenching and tempering process of SAE 52100 bearing steel was continuously monitored via in-situ dilatometry and high-energy X-ray diffraction, mapping the evolution of the constituent phases and lattice distortions and their direct correlation with observed dimensional changes of the material. During quenching from an austenitisation temperature of 860–50 °C, there was a continuous increase in lattice distortion in the parent austenite. Below the martensite start temperature of M S = 209 ± 15.0 °C, the c - lattice parameter and lattice distortion of the formed martensite initially decreased, then subsequently presented an increasing trend. An increase in sample length was detected only at martensite fractions ≥ 18 vol%, and occurred simultaneously with an increase in the c α' / a α' tetragonality ratio. An increase in sample length was detected during isothermal holding at 50 °C with a reduction in the martensite c α' parameter, potentially due to the expulsion of carbon. Tempering promoted the loss of martensite tetragonality at 283 ± 7.80 °C. At a tempering temperature of 340 °C, the austenite retained after quenching transformed completely within 1.5 min. The following reduction in sample length and expulsion of carbon from martensite is correlated to the relaxation of lattice distortion in the martensite-bainitic ferrite matrix. Graphical Abstract: ga1 Highlights: At M s = 209 °C, martensite with highest lattice distortion was observed. Sample length and tetragonality only increase when ~18 vol% of martensite formed. Holding at 50 °C (quench temperature), 2 vol% of martensite formed and c α' decreased. Tetragonality disappeared at 283 °C whilst heating to the tempering temperature. Austenite fully transformed into bainite after 1.5 min whilst tempering at 340 °C.